Response of fish tissue mercury in a freshwater lake to local, regional, and global changes in mercury emissions. (25th April 2014) - Vijayaraghavan, Krish; Levin, Leonard; Parker, Lynsey; Yarwood, Greg; Streets, David
Abstract A suite of mechanistic atmospheric and mercury (Hg) cycling and bioaccumulation models is applied to simulate atmospheric Hg deposition and Hg concentrations in the water column and in fish in a Hg‐impaired freshwater lake located in the northeastern United States that receives its Hg loading primarily through deposition. Two future‐year scenarios evaluate the long‐term response of fish tissue Hg concentrations to reductions in local and nationwide coal‐fired electric‐generating utility and other Hg emissions and an increase or decrease in global (non‐US) Hg emissions. Results indicate that fish tissue Hg concentrations in this ecosystem could require approximately 3 yr to 8 yr to begin to respond to declines in US emissions and deposition with a fish Hg reduction proportional to deposition reduction requiring over 50 yr. Furthermore, recovery could potentially be partially or completely offset by growth in non‐US Hg emissions. Environ Toxicol Chem 2014;33:1238–1247. © 2014 SETAC